Associations of Prediabetes, Diabetes and Glucose‐Related Markers With Cognition and Neuroimaging in a 2‐Year Multidomain Lifestyle Randomised Controlled Trial - Lorenzo, Thais; Ngandu, Tiia; Lehtisalo, Jenni; Antikainen, Riitta; Gispert, Juan Domingo; Kemppainen, Nina; Laatikainen, Tiina; Lindström, Jaana; Rinne, Juha; Soininen, Hilkka; Strandberg, Timo; Torre; et al. (Wiley, 2025)
Aims
Few longitudinal studies have explored Oral Glucose Tolerance Test markers (OGTT) and both cognitive and brain changes. We investigated OGTT and other glycaemia and insulin resistance markers, and cognitive and neuroimaging changes in the Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER).
Materials and Methods
At-risk individuals aged 60–77 years without dementia (N = 1259) were randomly enrolled in a 2-year multidomain lifestyle intervention or regular health advice program. 1025 participants without previously diagnosed diabetes underwent OGTT. Brain MRI scans were available for 132 participants and amyloid (PiB)-PET and FDG-PET scans for 47. Cognition was assessed using the modified Neuropsychological Test Battery (mNTB).
Results
Higher baseline dysglycaemia measures, particularly those from the OGTT, were connected to less favourable changes in multiple cognitive measures and hippocampal volume. Higher baseline triglyceride-glucose (TyG) index was associated with higher amyloid accumulation and decline in brain glucose metabolism. Higher baseline glycated haemoglobin (HbA1c) was related to favourable changes in processing speed and cortical thickness. There were no significant intervention-control differences in the change in glycaemia markers. Baseline dysglycaemia and glycaemia-related markers did not modify the previously reported intervention benefits on cognition.
Conclusions
Higher baseline dysglycaemia measures are linked to more deleterious changes in cognition. Specifically, OGTT measures may be the most sensitive for detecting subtle glycaemic abnormalities associated with both unfavourable cognitive and neuroimaging changes. However, HbA1c shows mixed associations with cognition and neuroimaging in people at risk of dementia without previously diagnosed diabetes. This study emphasises the importance of more accurate glucose-related markers when investigating early stages of glucose metabolism abnormalities and their relationship to subtle cognitive impairment and its structural brain correlates.